2013
DOI: 10.1161/atvbaha.113.301755
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow– or Vessel Wall–Derived Osteoprotegerin Is Sufficient to Reduce Atherosclerotic Lesion Size and Vascular Calcification

Abstract: Objective— Osteoprotegerin (OPG) is a decoy receptor for the osteoclast differentiation factor receptor activator of NF-κB ligand. OPG regulates bone homeostasis, and its inactivation in mice results in severe osteoporosis. OPG deficiency in apolipoprotein E (ApoE) −/− mice results in increased atherosclerotic lesion size and calcification. Furthermore, receptor activator of NF-κB ligand enhances macrophage-dependent smooth muscle cell calcification in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 55 publications
1
31
0
3
Order By: Relevance
“…Knockout of osteoprotegerin, the inhibitor of receptor activator of nuclear factor-κB ligand-dependent osteoclast formation, leads to reduced lesion calcification. 37,38 Similarly, VSMC-specific knockout of Runx2 reduced the level of receptor activator of nuclear factor-κB ligand and subsequent osteoclast differentiation of macrophages and thereby inhibited atherosclerotic calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout of osteoprotegerin, the inhibitor of receptor activator of nuclear factor-κB ligand-dependent osteoclast formation, leads to reduced lesion calcification. 37,38 Similarly, VSMC-specific knockout of Runx2 reduced the level of receptor activator of nuclear factor-κB ligand and subsequent osteoclast differentiation of macrophages and thereby inhibited atherosclerotic calcification.…”
Section: Discussionmentioning
confidence: 99%
“…11 Vessel wall-derived OPG was able to inhibit calcium deposition in ApoE−/− OPG−/− knockout animal models, indicating the ability of endogenous OPG to inhibit vascular calcification, further suggesting that systemic elevation of OPG may be an adaptive response factor. 12 Taken together, it remains unclear whether targeting RANK-RANKL may have a role in modifying vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion and migration of inflammatory cells produce an oxidizing environment, which is critical for the progression of vascular diseases. 27 demonstrated that osteoprotegerin derived from the bone marrow block the progression of vascular calcification. 27 About the pathogenesis of aneurysms, Marinkovic et al 28 performed an interesting study to limit aneurysm growth by inhibition of inflammation and reducing EC activation with immunosuppressive drug azathioprine.…”
Section: Adventitial Tissues and Inflammatory Cells For Vascular Funcmentioning
confidence: 99%
“…27 demonstrated that osteoprotegerin derived from the bone marrow block the progression of vascular calcification. 27 About the pathogenesis of aneurysms, Marinkovic et al 28 performed an interesting study to limit aneurysm growth by inhibition of inflammation and reducing EC activation with immunosuppressive drug azathioprine. They showed that azathioprine has an anti-inflammatory effect in ECs and inhibits Rac1 and c-Jun-terminal-N-kinase activation, which may explain its protective role in the development of aneurysm formation and severity.…”
Section: Adventitial Tissues and Inflammatory Cells For Vascular Funcmentioning
confidence: 99%